Assessment of strategies for improving adult literacy programmes in Nigeria - Ejiro-Mitaire, F. O.; Ezeyili, P. N. (Journal of Research in Adult and Continuing Education, 2023)
This study examined the concepts of adult literacy and its prominent position in the hallmark of education. It gives an overview of adult literacy in Nigeria, its relevance and outlines its components. The paper assessed strategies to improve adult literacy programmes. Finally, the paper concludes by recommending that adult educators should seek ways to adequately utilize the strategies of improving Adult literacy programmes and Government should be involved in literacy programmes from inception to finish.